Comparative analysis of Ligusticum chuanxiong from Gansu and Sichuan using the fingerprint technique and HS-SPME-GC-MS combined with chemometric analysis - Jialing Zhang; Juanjuan Liu; Yiyang Chen; Liangcai Wang; Ke Li; Gonghan Tu; Xiaohui Ma; Ling Jin (PLoS ONE, 2026)
Ligusticum chuanxiong (LC) is an important medicinal herb widely used in traditional Chinese medicine (TCM). The variety cultivated in Gansu Province, known as chuanxiong ( Xixiong, LX), exhibits distinct morphological characteristics compared with LC from other regions. In this study, we performed a comprehensive comparative analysis of LC and LX. Odor and color were quantified using an electronic nose and a colorimeter, respectively. Volatile components were profiled by headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS), while high-performance liquid chromatography (HPLC) was used to quantify chemical constituents and establish chromatographic fingerprint profiles. Pearson correlation analysis was further conducted to elucidate the relationships among chromaticity parameters, odor and other phenotypic traits, and chemical constituents, as well as their associations with altitude. Results showed that LX had significantly greater dry weight, diameter, and other morphological parameters than LC. LX powder displayed a brown hue, whereas LC powder appeared yellowish-brown. LC exhibited higher response values for the W1S and W2S sensors compared with LX. HPLC analysis revealed that the contents of ligustilide (LI), senkyunolide I (SI), senkyunolide H (SH), and 3-butylphthalide (3B) were significantly higher in LC than in LX ( p < 0.01), whereas the senkyunolide (SA) was significantly lower in LC ( p < 0.05). HS-SPME-GC-MS detected 82 compounds in LX and 62 compounds in LC, with 34 compounds shared between them. Significant correlations were observed among altitude, chromaticity, odor, and chemical composition. This study provides a systematic characterization of the differences between the collected LC and LX, offering insights that may enhance the market competitiveness of LX, promote optimal utilization of regional resources, and support the sustainable development of the LX industry in Gansu Province.